The politics of resource bargaining, social relations and institutional development in Zimbabwe since independence - Richard Saunders (United Nations Research Institute for Social Development (UNRISD), 2019)
This paper examines evolving models and experiences of domestic resource mobilization in Zimbabwe since independence in 1980. Grounded in UNRISD's Politics of Domestic Resource Mobilization and Social Development project, the study explores key questions around the nature and dynamics of resource bargaining over revenue mobilization and allocation; the changes in relationships among key actors; and the forms and outcomes of institutional development surrounding resource bargaining processes. It adopts a historicalcomparative approach to explore the evolving balance of forces among actors and emerging institutional constraints that are seen as catalyzing the formulation of successive resource mobilization strategies and associated development outcomes. Three case studies of divergent resource mobilization innovations underscore the complexity of challenges faced by governments whose actions are shaped by uneven state capacity and policy autonomy; a weak formal sector in which established business actors wield significant power and influence; and growing contestation over legitimacy and participation by political and social actors. The Zimbabwean case underscores the critical importance of political undercurrents and contesting interests in resource bargaining and the shaping of development policy. It also highlights the uneven nature of social actors' access to and influence in bargaining processes; and of the state itself, in the wake of neoliberal austerity, state capture and intra-elite competition. At the same, the study finds, evidence from Zimbabwe points to the benefits of more transparent, inclusive and capacitated forms of revenue mobilization involving a wider array of social actors.
Keywords: 330